Evaluation and characterization during the anaerobic digestion of high-strength kitchen waste slurry via a pilot-scale anaerobic membrane bioreactor. (October 2015) - Xiao, Xiaolan; Huang, Zhenxing; Ruan, Wenquan; Yan, Lintao; Miao, Hengfeng; Ren, Hongyan; Zhao, Mingxing
Highlights: The high-strength kitchen waste slurry was reliably treated via an AnMBR. The precipitation and agglomeration of LCFAs and Ca 2+ influenced the treatment. SRT control was significant to methane recovery enhancement in the digestion. SRT control was significant to membrane fouling mitigation in the digestion. Abstract: The anaerobic digestion of high-strength kitchen waste slurry via a pilot-scale anaerobic membrane bioreactor (AnMBR) was investigated at two different operational modes, including no sludge discharge and daily sludge discharge of 20 L. The AnMBR provided excellent and reliable permeate quality with high COD removal efficiencies over 99%. The obvious accumulations of long chain fatty acids (LCFAs) and Ca 2+ were found in the anaerobic digester by precipitation and agglomeration. Though the physicochemical process contributed to attenuating the free LCFAs toxicity on anaerobic digestion, the digestion efficiency was partly influenced for the low bioavailability of those precipitates. Moreover, higher organic loading rate (OLR) of 5.8 kg COD/(m 3  d) and digestion efficiency of 78% were achieved as the AnMBR was stably operated with sludge discharge, where the membrane fouling propensity was also alleviated, indicating the crucial significance of SRT control on the treatment of high-strength kitchen waste slurry via AnMBRs.